Soil temperature and agronomic implications in two regions of the State of São Paulo, Brazil - Nasser, Maurício Dominguez; Bardiviesso, Estefânia Martins; Aguilar, Ariel Santivañez; Zonta, Augusto (Scientia Agraria Paranaensis, 2020)
Plants can tolerate a wide range of soil temperature variations, but their development is affected when the soil undergoes higher or lower temperatures of certain extreme values. The aim of this study was to assess the soil temperature of two regions of the state of São Paulo, Brazil. Daily measurements of soil temperature were taken at two weather stations, one in the municipality of Adamantina (soil classified as Podzolic, Dark Red Latosol, Eutrophic, moderate A, of sandy/medium texture) and another in the municipality Monte Alegre do Sul (soil classified as Red Yellow Podzolic, of fine sandy-clayey texture) within a period of 365 days. The experimental design was completely randomized, with the two municipalities being the treatments, and 12 repetitions determined by monthly averages. The soil temperature at a 3-cm depth in Adamantina reached values above 40°C, values not observed in Monte Alegre do Sul. At a 12-cm depth, there were no differences between the municipalities. In Monte Alegre do Sul, the recorded soil temperatures proved suitable for crops, with better use of organic matter by the soil and greater stability of surface temperature throughout the day compared to Adamantina. In Adamantina, however, the use of agronomic technology is required to ensure greater stability of surface temperature. The temperature throughout the year in the soil surface layer in the Adamantina region in the afternoon was higher than in the Monte Alegre do Sul region, a fact that implies the need of differentiated agronomic technology depending on the cultivation location.